The political and scientific efforts of Imam Sanhoon and ibn al-Furat in the era of al-Aaghalyah State ( 184-296AH) - Ghan Uraibi, Sundos (Al-Adab Journal, 2019)
The establishment of the Aghlabid state (184-296 / 800-908) was closely linked to the chaos, sectarian strife, and revolts of the Arab and Berber armies. The efforts of the Aghlabid princes, who were able to establish a large military force of Westernized Berbers and worked on the recruitment of military personnel in the Algerian army enabled the Aghlabid to spread security and stability in the Lower Maghreb (Tunisia). The scientific movement witnessed a great prosperity since the capital of their state Kairouan, a pole of cultural culture in which the flags of their scientific and political status emerged, led by the Kairouan judge and Fath Sicilian Assad ibn al-Furat Combine science and science Jihad members and, for the sake of Allah and Imam Sahnoun bin Said , who was most famous scholars of Maliki in the Islamic Maghreb